Quantitative cell lysis of indigenous microorganisms and rapid extraction of microbial DNA from sediment. - Moré, M I (1994)
This study reports improvements in two of the key steps, lysis of indigenous cells and DNA purification, required for achieving a rapid nonselective protocol for extracting nucleic acids directly from sodium dodecyl sulfate (SDS)-treated sediment rich in organic matter. Incorporation of bead-mill homogenization into the DNA extraction procedure doubled the densitometrically determined DNA yield (11.8 micrograms of DNA.g [dry weight] of sediment-1) relative to incorporation of three cycles of freezing and thawing (5.2 micrograms of DNA.g [dry weight] of sediment-1). The improved DNA extraction efficiency was attributed to increased cell lysis, measured by viable counts of sediment microorganisms which showed that 2 and 8%, respectively, survived the bead-mill homogenization and freeze-thaw procedures. Corresponding measurements of suspensions of viable Bacillus endospores demonstrated that 2 and 94% of the initial number survived. Conventional, laser scanning epifluorescence phase-contrast, and differential interference-contrast microscopy revealed that small coccoid bacterial cells (1.2 to 0.3 micron long) were left intact after combined SDS and bead-mill homogenization of sediment samples. Estimates of the residual fraction of the fluorescently stained cell numbers indicated that 6% (2.2 x 10(8) cells.g [dry weight] of sediment-1) of the original population (3.8 x 10(9) cells.g [dry weight] of sediment-1) remained after treatment with SDS and bead-mill homogenization. Thus, lysis of total cells was less efficient than that of cells which could be cultured. The extracted DNA was used to successfully amplify nahR, the regulatory gene for naphthalene catabolism in Pseudomonas putida G7, by PCR.(ABSTRACT TRUNCATED AT 250 WORDS)